Practical Guide for Anticoagulant and Antiplatelet Reversal in Clinical Practice - Mohammed Aldhaeefi; Hisham A. Badreldin; Faisal Alsuwayyid; Tariq Alqahtani; Omar Alshaya; Majed S. Al Yami; Khalid Bin Saleh; Shmeylan A. Al Harbi; Abdulrahman I. Alshaya (MDPI AG, 2023)
In recent years, anticoagulant and antiplatelet use have increased over the past years for the prevention and treatment of several cardiovascular conditions. Due to the rising use of antithrombotic medications and the complexity of specific clinical cases requiring such therapies, bleeding remains the primary concern among patients using antithrombotics. Direct oral anticoagulants (DOACs) include rivaroxaban, apixaban, edoxaban, and betrixaban. Direct thrombin inhibitors (DTIs) include argatroban, bivalirudin, and dabigatran. DOACs are associated with lower rates of fatal, life-threatening, and significant bleeding risks compared to those of warfarin. The immediate reversal of these agents can be indicated in an emergency setting. Antithrombotic reversal recommendations are still in development. Vitamin K and prothrombin complex concentrate (PCCs) can be used for warfarin reversal. Andexanet alfa and idarucizumab are specific reversal agents for DOACs and DTIs, respectively. Protamine sulfate is the solely approved reversal agent for unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH). However, there are no specific reversal agents for antiplatelets. This article aims to provide a practical guide for clinicians regarding the reversal of anticoagulants and antiplatelets in clinical practice based on the most recent studies.